Resisting neoliberalism in education : local, national and transnational perspectives - Tett, Lyn, 1946-; Hamilton, Mary, 1949- (Policy Press scholarship online., 2019)
Neoliberalism is having a detrimental impact on wider social and ethical goals in the field of education. Using an international range of contexts, this book provides practical examples that demonstrate how neoliberalism can be challenged and changed at the local, national and transnational level.